Consensus and source properties of Malaysian aggregates for superior performing asphalt pavements / Juraidah Ahmad, Mohd Yusof Abdul Rahman and Zainab Mohamed - Ahmad, Juraidah; Abdul Rahman, Mohd Yusof; Mohamed, Zainab (Research Management Institute (RMI), 2008)
Aggregates and binder are the two main constituents that make up hot mix asphalt (HMA). Since a wide variety of mineral aggregate is used to produce Hot Mix Asphalt (HMA), proper evaluation of the mineral aggregate properties is important to ensure good performance of asphalt mixture. Unlike Superpave system, Marshall and Hveem method do not incorporate aggregate criteria into their procedures. The Superpave Highway Research Programme (SHRP) modified the Delphi process to include aggregate properties which are divided into two categories; consensus and source. The consensus properties include aggregate angularity, flat and elongated particles and sand equivalent to ensure aggregate quality is sufficient to provide satisfactory HMA performance for all design traffic levels. The source properties are often used to qualify local source of aggregate which include abrasion, deleterious materials and soundness test. In this study, granite aggregates were collected from northern, central and southern region of Peninsular Malaysia. Results of the aggregate testing showed that Malaysian aggregates are durable and of good quality. These aggregates conformed to the criteria as required in the Superpave system, hence suitable for use in the mix design.